AN ANALYSIS OF READING EXERCISES QUESTION INSERTED IN ENGLISH BOOK ORIENTED TO HOTS FOR THE TENTH GRADE STUDENTS OF SMKN 1 PENUKAL UTARA - Doraimon; Masagus Firdaus; Hanni Yukamana (Esteem Journal of English Education Study Programme, 2025)
English, as the lingua franca of our interconnected world, holds immense significance for contemporary students. Its status as a global language transcends borders, enabling communication across diverse cultures, industries, and regions. Proficiency in English is not merely a skill but a gateway to numerous opportunities, such as accessing international academic resources, participating in global job markets, and fostering cross-cultural understanding. This research underscores the critical role of English in modern education, highlighting its function in facilitating global collaboration and access to critical educational resources. Most scholarly literature and leading educational materials are in English, making proficiency in the language essential for keeping up with developments across various fields.This study employed a qualitative research design to explore the role of the "Work in Progress" English textbook within the learning environment at SMKN 1 Penukal Utara. The qualitative approach enabled an in-depth examination of students' perceptions of the textbook, their responses to its teaching methodology, and the contribution of the textbook to their English language proficiency. Findings from the study reveal that the textbook incorporates a significant number of Higher Order Thinking Skills (HOTS) questions, particularly for 10th-grade students. Approximately 70% of the textbook's content focuses on enhancing students' analytical and problem-solving skills, aligning with its overarching goal of deepening students' understanding of the English language. The integration of HOTS questions in each thematic unit significantly contributes to the development of students' higher-order thinking abilities.